Influence of gas pressure on high-order-harmonic generation of Ar and Ne - Wang, Guoli; Jin, Cheng; Le, Anh-Thu; Lin, C. D. (My University, 2011)
We study the effect of gas pressure on the generation of high-order harmonics where harmonics due to individual atoms are calculated using the recently developed quantitative rescattering theory, and the propagation of the laser and harmonics in the medium is calculated by solving the Maxwell's wave equation. We illustrate that the simulated spectra are very sensitive to the laser focusing conditions at high laser intensity and high pressure since the fundamental laser field is severely reshaped during the propagation. By comparing the simulated results with several experiments we show that the pressure dependence can be qualitatively explained. The lack of quantitative agreement is tentatively attributed to the failure of the complete knowledge of the experimental conditions.